Concrete surface coatings and the influence of substrate moisture condition on bond strength - Kay, Sean (Department of Civil Engineering, 2016)
Concrete structures, in particular reinforced concrete structures, have been designed and built for many years. Many previously built structures are now being compromised with regard to their condition and structural integrity. There has developed a need to maintain these structures and protect them in order to protect the users and minimise the expenses associated with repair and maintenance. Instead of resorting to demolishing and rebuilding, engineers are becoming increasingly capable of restoring and enhancing existing structures in order to maximise the original structures lifespan. One of the ways in which this is achieved is through the implementation of various repair and maintenance strategies. These strategies can range from cathodic protection of the steel reinforcement to increasing concrete cover of the section. The easiest and often most commonly used method, although often not effective when used on its own, is to coat the concrete surface with a decorative or protective coating. There are many coatings available, ranging from simple to complex formulations of inorganic and/or organic materials. These coatings each perform a unique function and will often be designed to combat a specific problem which the structure is exposed to. The formulation of the coatings are almost always designed correctly when they are manufactured, however, premature bond failure due to poor substrate surface preparation and various substrate moisture conditions still seem to occur after coating application. This investigation will give insight into the effects a sound, clean and profiled concrete substrate that is subjected to different moisture conditions will have on the bond strength achieved when using cementitious based coatings. The reason for differing the moisture conditions of the substrate is that often on site the moisture condition of an existing substrate is not known prior to application of the coating. Through this investigation, epoxy modified cementitious coatings have been shown to provide an acceptable bond strength. In some cases, failure within the coating instead of the acceptable failure within the substrate has resulted, due only to the level of dryness of the substrate. A thorough investigation on the theory behind surface coatings, their properties and performance requirements was done and subsequently followed by a detailed experimental programme that was performed and analysed to provide insight to the said coating behaviour.